The rear foot elevated split squat - Wing, C. (Journal of Australian Strength and Conditioning, 2018)
The rear foot elevated split squat is a popular unilateral exercise within strength and conditioning programmes for use within both performance enhancement and injury prevention settings. Due to the particular demands of the lift, the athlete`s levels of mobility and stability, alongside strength, are also challenged. This article provides a detailed outline of the technical demands of the lift, as well as offering advice on how to correct common errors and provides practical variations.